Free Ammonia Deliming: Effect of Tartaric Acid Addition as a Deliming Agent on The Quality of Wet Blue and Wastewater - A. W. Nugraha; O. Suparno; N. S. Indrasti; Hoerudin Hoerudin (Faculty of Animal Science, Bogor Agricultural University, 2020)
The objective of this study was to evaluate the pelt and wastewater characteristics after deliming process in an acid condition by tartaric acid, also wet blue properties that were formed. Various observed variables were the dose of tartaric acid, pelt thickness, calcium content, physical and chemical properties of wet blue, such as tensile strength, tear strength, elongation, shrinkage temperature, and chrome oxide content, as well as the pollutants content of wastewater as chemical oxygen demand (COD), biological oxygen demand (BOD), total suspended solid (TSS), and total dissolve solid (TDS). The experiment used a completely randomized design with a factorial arrangement. The first factor was pH variables consisted of 3 levels, i.e., 4, 5, and 6 in the final deliming solution. The second factor was the deliming time consisted of 3 levels, i.e., 45 min, 60 min, and 75 min. Data were analyzed using Analysis of Variance (ANOVA) and then Duncan’s Multiple Range Test (DMRT). The results showed that deliming for 60 min and the pH of 5 at the end of the solution was the best treatment to remove calcium content in the pelt and reduce the thickness of pelt. It did not affect the physical and chemical quality, such as tensile strength, tear strength, elongation at break, and shrinkage temperature of the wet blue produced. Also, the quality of wastewater produced was better than the use of ammonium sulfate as a deliming agent. It can be concluded that the use of tartaric acid as pH regulator of deliming stage at pH 5 for 60 min can be used as an alternative deliming agent to substitute ammonium sulfate.